Study of pharmacy websites in Ukraine as a component of telepharmacy - Dorykevych, Kateryna; Kurylo , Kateryna; Hrushkovska , Dzvenyslava (Annals of Mechnikov's Institute, 2023)
Introduction. Telepharmacy is a promising area of providing pharmaceutical assistance, it is actively developing in Ukraine, therefore the subject of our research was the websites of pharmacies and services that provide electronic trade in medicinal products and have an informational component. Material & methods. We used the methods of system approach, analysis, synthesis, comparison, generalization, content analysis (content analysis of web-sites included the study of their structure, information content and ease of use) and the survey method (for conducting the survey we developed a questionnaire consisting of two blocks of questions: social profile of the respondents and questions related to the issues of the research). The research materials were: normative legal acts regarding the online trade of medicinal products in Ukraine and the European Union, scientific publications on the implementation of telepharmacy as a direction of practical pharmacy in Ukraine and in the world, websites of pharmacies and services for the online sale of medicinal products, and the results of our own research. Results & discussion. The study of the websites of domestic pharmacies and services (10 pharmacy websites and two services) showed that, in general, the structure of the websites is concise, navigation and search are convenient, the loading speed is high, and the design is dominated by white, blue and green colors. The websites are characterized by the function of sorting by price and rating, the function of online purchase, discounts for online purchases, as well as offers of promotional and profitable products, popular brands and "novelties", the option of delivery by mail or courier delivery (5 from 12 sites), a developed network of modern communications (blogs, social media, feedback), the use of own original product classifications and the format of presenting information about medicinal products. To study the practice of using websites, a questionnaire was developed and a pilot survey of pharmacy visitors was conducted (55 people were interviewed). It was found that 65.5% of respondents use the search and reservation of medicines and medical products; reasons for refusing to use websites are: lack of need (18.2%) and habit (12.7%), as well as skills (9.0%); in the opinion of 69.1% of respondents, the website should provide basic information about medicines (instructions, cost, availability in pharmacies, conditions of promotions); reasons for using websites: convenience (36.4%), economy (12.7%) and all together ("convenient, economical, faster") (38.2%); the website should also include information about the pharmacy schedule (72.7%), pharmacy contacts (70.9%), and a map of the pharmacy network (65.5%); at the moment, the information content on the websites is sufficient (43.6%), while there is a lack of comparative data on prices (40.0%), a list of additional services (23.6%), and conditions for returning goods (21.8%); 70.9% of respondents have a positive attitude to electronic trade in medicines. Concliusions. Pharmacy websites are actively used by consumers to book and buy medicines, related products of the pharmacy range, as well as to obtain information about them. The results of this study can be used to optimize the operation of sites and expand online services by pharmacies. The prospect of further research consists in studying the possibilities of implementation of other components of telepharmacy in Ukraine. Keywords: drug, pharmacy, telepharmacy, pharmacy websites.